Thermal analysis as a screening technique for the characterization of babassu flour and its solid fractions after acid and enzymatic hydrolysis - de Almeida, Rafael Ramires; Lacerda, Luiz Gustavo; Murakami, Fabio Seigi; Bannach, Gilbert [UNESP]; Demiate, Ivo Mottin; Soccol, Carlos Ricardo; da Silva Carvalho Filho, Marco Aurelio; Schnitzler, Egon (Elsevier B.V., 2011)
The babassu (Orbignya phalerata) is a native tree found in northern Brazil. Extracts of the babassu coconut have been widely used in industry. Babassu flour has about 60% starch, thus, besides nourishment it can be used as an alternative biofuel source. However, the properties of this starch lack of study and understanding. The main purpose of this study was to investigate the thermal behavior of raw babassu flour and its solid hydrolyzed fraction. The analyses were carried out using SHIMADZU DSC and TG thermic analyzers. The results demonstrated a reduction in thermal stability of the solid hydrolyzed fraction compared to raw matter. The kinetic parameters were investigated using non-isothermal methods and the parameters obtained for its decomposition process were an E(a) of 166.86 kJ mol(-1) and a frequency factor (beta) of 6.283 x 1014 min(-1); this was determined to be a first order reaction (n = 1). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Babassu flour; Hydrolysis; DSC; TG; Kinetics analysis